(untitled) (IASH Indian Journal of Arid Horticulture, 2026)
The study evaluated the frequency of fungal infections in fig and their economic implications across 100 orchards in the Purandar region, Maharashtra. Rust-related pathogens (Cerotelium fici or Phakopsora sp.) were the most common disease, appearing in 75% of assessed farms, with 25% reporting concomitant infections such as leaf blight and mite infestations. Economic analysis indicated that 50% of farms suffered substantial income loss, with an average market disruption score of 3.25 on a 5-point scale. According to regression analysis, yield was more strongly predicted by farm size (β = 2.517) than by years of expertise (β = 0.228). The research underscores the pressing necessity for rust-resistant cultivars, comprehensive disease management, and focused extension initiatives to guarantee the enduring viability of fig farming in the Purandar region.